Perayaan Obon (Obon-Matsuri) di Jepang - Reny Wiyatasari (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
The purpose of this study is to describe the Obon celebration (Obon-matsuri) by Japanese society today. The data used are several literature on Obon and interviews with several informants, namely Japanese people who have or still do the Obon-matsuri ritual. The research method used is a qualitative-descriptive. Data collection with library studies, observations, and interviews to explore deeply about the experiences of informants related to Obon in the past and present. In analyzing data, researchers used the qualitative data analysis techniques. The results of this study are indicate that the differences in Obon celebrations today with the previous period are: 1)  Fewer Japanese people, especially those living in cities, celebrate Obon. Obon as an opportunity for Japanese people to visit their parents/ grandparents or main family, and together with them celebrating Obon becomes increasingly rare or difficult to do; 2) As fewer Japanese people celebrate Obon with their main families, the activities of performing Obon rituals are increasingly rare. Meanwhile, two things that are still maintained from the past to the Obon celebration are: 1) Japanese society is still regularly doing ohakamairi, and 2) Obon is still interpreted and believed that during these days the spirits of ancestors return to their former homes.